2013
DOI: 10.1002/hed.23261
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the pretreatment serum level of cytokeratin fraction 21‐1 in undifferentiated nasopharyngeal carcinoma: A study of 332 cases

Abstract: The pretreatment serum level of CYFRA 21-1 would be a reliable biomarker to evaluate the long-term prognosis of patients with undifferentiated NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…According to the stage, CYFRA21-1 could be the most important prognostic factor in predicting the outcomes of patients with malignant tumors, and the serum level of CYFRA21-1 could be used as a powerful prognostic marker in NPC. Wei et al [22] demonstrated that the pretreatment serum level of CYFRA21-1 could be a reliable biomarker for evaluating the long-term prognosis of patients with undifferentiated NPC. In our study, the relationship between the clinical objective tumor response and serum CYFRA21-1 change in patients submitted to systemic clinical treatment was synchronized.…”
Section: Discussionmentioning
confidence: 99%
“…According to the stage, CYFRA21-1 could be the most important prognostic factor in predicting the outcomes of patients with malignant tumors, and the serum level of CYFRA21-1 could be used as a powerful prognostic marker in NPC. Wei et al [22] demonstrated that the pretreatment serum level of CYFRA21-1 could be a reliable biomarker for evaluating the long-term prognosis of patients with undifferentiated NPC. In our study, the relationship between the clinical objective tumor response and serum CYFRA21-1 change in patients submitted to systemic clinical treatment was synchronized.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially common in Guangdong, Guangxi, and other regions in China, and its incidence rate is as high as 20-30/100,000 per year. 1 Epidemiological and experimental studies have shown that genetic susceptibility, Epstein–Barr virus (EBV) infection, and environmental factors are specific and multifactorial causes of NPC. 2 Although many people are exposed to EBV infection and ecological risk factors, including heavy smoking and alcohol consumption, only a small proportion of the population has developed NPC, indicating that individual genetic susceptibility may play a more important role in the carcinogenic mechanism of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, its incidence is up to 20–30/100,000 per year. 1 Mechanisms of NPC onset and progression remain unknown, though they are thought to be related to genomic DNA damage, as in many other malignant tumors. 2 , 3 Oxidative DNA damage is one of the most frequent causes of malignant tumors, and 7,8-dihydro-8-oxoguanine is one of the best characterized oxidative DNA lesions.…”
Section: Introductionmentioning
confidence: 99%